Is it too early to condemn early sport specialisation? - Baker, J.; Mosher, A.; Fraser-Thomas, J. (British Journal of Sports Medicine, 2021)
There has been a rapid and substantial increase in scholarly and public discourse regarding the perceived consequences of single sport specialisation during periods of early development. Since 2017, there have been three systematic reviews and 10 narrative reviews/editorials about the negative implications of specialisation in sport. A 2009 review in this area asked `what do we know about early sport specialisation` and concluded `not much`. In this editorial, we argue things have not changed much in the intervening decade, despite the considerable increase in rhetoric round this subject. It will be important to better understand coach and other key stakeholder viewpoints on this issue since their voice has been largely absent from this discussion. If we under-stand the mechanisms driving positive and negative outcomes in both specialised and non-specialised environments, we can improve how sport is delivered in all settings.